The Effect of Exchange, SBIS, and Profit-Based Financing on The Level of Risk of Financing Problems - Willa Fatika Sari; Miftahul Mahrus; Yasmin Yasmin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine the effect of exchange rates, Bank Indonesia Sharia Certificates (SBIS), and profit-based financing on the level of risk of financing problems in Sharia Commercial Banks in Indonesia. The data used were the secondary data from January 2015 to October 2021. The population was the Sharia Commercial Bank in Sharia Banking Statistics published by the Financial Services Authority (OJK), by using non-probability sampling technique. The data analysis used was multiple linear regression using STATA software. The results of this study indicate that partially the independent variable namely the exchange rate has an insignificant negative effect on the risk level of problem financing. Moreover, SBIS has a significant negative effect on the level of risk of non-performing financing, and profit-based financing has a significant negative effect on the level of risk of financing problems.